Accounting information system of saving and loan Cooperative at PT. Pelabuhan Indonesia II Jambi (Persero) - Rezagi Meilano (Journal of Applied Accounting and Business, 2019)
Purpose – The purpose of this study is to find out how the savings and loan accounting information system that runs on PT. Pelabuhan Indonesia II (Persero) and to design a savings and credit accounting information system at PT. Pelabuhan Indonesia II (Persero). Design/methodology/approach – The analytical tool used is covering system analysis, which then proceed to the system design stage using flowcharts and DFD. Findings – Based on the results of the study the authors found that the system that is run by the cooperative still has shortcomings and weaknesses in terms of member data collection procedures to the transactions carried out, the recording of loan transactions, and the reports produced. Originality/value – This research was conducted at the Cooperative of PT. Pelabuhan Indonesia II (Persero) which is still using a manual system. Researcher designs an accounting information system that is able to overcome these weaknesses and shortcomings.